The Amazing Race : on resources, conflict, and cooperation in the Arctic - Palosaari, Teemu (2012)
The article uncovers factors that point towards continuing peaceful development in the Arctic. Contrast to the grim visions of an Arctic Race to the resources, there is a process where international law, UN conventions, environmental regimes and scientific guidelines are followed. Consequently, the main security challenges in the Arctic are not related to traditional interstate security questions. Instead of issues like maritime delimitation or cold water military capacities we should be more concerned about human and environmental security. To this end, the article analyses the local dilemma between traditional means of livelihood and modern hydrocarbon industry, global environmental impacts of glacier melting, and moral issues related to the utilization of the new Arctic oil and gas resources (the so-called Arctic paradox). NGP yearbook 2011 : sustainable development in the Arctic region through peace and stability / Lassi Heininen & Regis Rouge-Oikarinen (eds.). ISBN 978-951-42-9758-8